Euroscepticism and EU cohesion policy: The impact of micro-level policy effectiveness on voting behaviour - Julia Bachtrögler; Harald Oberhofer (Austrian Institute of Economic Research (WIFO), 2018)
This study investigates whether there is a link between the successful implementation of European co-hesion policy and the voters' attitudes towards the EU. Using the French presidential elections in 2017 as a case study, we do not solely consider regional funds expenditures but also its induced effects in a re-gion as further potential determinant of pro-European or eurosceptic voting behaviour. In order to measure the effectiveness of EU structural funds and Cohesion Fund assignment, firm-level employment effects in French NUTS-2 regions stemming from project allocation during the multi-financial framework 2007-2013 are estimated. The obtained average treatment effects are, in a next step, used together with other regional characteristics to capture the citizens' perceived exposure to the EU in an empirical voting model for the French presidential election in 2017. The estimation results reveal a significant negative relationship between the effectiveness of EU funds allocation and the vote share of the eurosceptic candidate Marine Le Pen.
Keywords: C21; D72; E61; R11; R58; 330; Euroscepticism; EU cohesion policy; effectiveness; voting behavior; French presidential election